PROFIL PELEPASAN NATRIUM DIKLOFENAK DARI TABLET LEPAS LAMBAT DENGAN PENAMBAHAN METHOCEL K15M SEBAGAI MATRIKS INTRAGRANULAR - S, T. N. Saifullah; Indriyani, Mike (Indonesian Research Gateway)
The slow release of drug from tablets dosage form obtained by adding cellulose derivative as matrix which could gel form. The aims of the study were to investigate the profile and the rate of diclofenac sodium release from sustained released tablets using Methocel K15M as matrix intragranular in medium with intestine pH. Diclofenac sodium sustained release were made with wet granulation method in five formulas based on the different concentration of Methocel K15M that added of 0mg (F Control), 25mg (F I), 50mg (F II), 75 mg (F III) dan 100mg (F IV). Dissolution testing used paddle stirrer with 100 rpm in a buffer phosphate medium of pH 7,6 at 37±0,5oC for 5 hours. Sampel analyzed by spectrophotometer at 274 nm. The result showed that the Methocel K15M matrix decreased the diclofenac sodium release from the tablets and it had a linear relationship with time. The more Methocel K15M added in the matrix the slower the rate of diclofenak sodium released from it. Drug release from the matrix followed zero order kinetics and mechanisms was a combination of erosion and diffusion, the diffusion mechanism was the dominant one. The results of t test with 95% confidence level the significant differences between four formulas. ABSTRAK Pelepasan obat secara perlahan dari sediaan lepas lambat dapat diperoleh dengan penambahan turunan selulosa sebagai matriks yang dapat membentuk gel. Penelitian ini bertujuan untuk mengetahui profil pelepasan natrium diklofenak dari tablet lepas lambat dengan penambahan Methocel K15M sebagai matriks intragranular dalam medium pH usus. Sediaan lepas lambat natrium diklofenak dibuat dengan cara granulasi basah dalam 5 formula yang didasarkan pada perbedaan kadar Methocel K15M yang ditambahkan, yaitu 0 mg (F Kontrol), 25mg (F I), 50mg (F II), 75 mg (F III) dan 100mg (F IV). Uji disolusi menggunakan pengaduk dayung dengan kecepatan pengadukan 100 rpm dalam medium dapar fosfat pH 7,6 pada suhu 37±0,5oC selama 5 jam. Sampel dianalisa secara spektrofotometri UV pada panjang gelombang 274 nm. Hasil uji disolusi menunjukkan kecepatan pelepasan obat dari matriks Methocel K15M berlangsung secara perlahan dan mempunyai hubungan yang linear dengan waktu. Semakin banyak Methocel K15M yang ditambahkan dalam matriks semakin lambat natrium diklofenak dilepaskan. Pelepasan natrium diklofenak dari matriks mengikuti kinetika orde nol dengan mekanisme kombinasi difusi dan erosi, mekanisme difusi lebih dominan.